Evaluation of In-brace Correction in Individuals with Adolescent Idiopathic Scoliosis: A Retrospective and Descriptive Study - Putra, Raden Achmad Candra; Limskul, Danaithep; Yotnuengnit, Pattarapol; Promsang, Trai; Kuptniratsaikul , Somsak (Open Access Macedonian Journal of Medical Sciences, 2022)
Introductions: Achieving maximum correction at the beginning of brace treatment in AIS is the only factor that can be controlled by the bracing provider if we have a better understanding of the prognostics and factors associated with achieving in-brace correction. The aim of this present study was to evaluate in-brace correction in a cohort of AIS patients who were treated by full-time bracing with plastic moulded thoraco-lumbo-sacral spinal orthosis (TLSO). Methods: This study was a retrospective descriptive study. We collected data from medical records of individuals with AIS who receiving full-time braces treatment from Orthotic Clinic, King Chulalongkorn Memorial Hospital. Demographic data included age, gender, weight, height, and body mass index (BMI). Cobb angle, Risser sign, and curve type were determined using pre and post-brace standing posteroanterior (PA) radiographs. Correlation analysis was performed to investigate in-brace correction with associated factors. Results: We included 91 patients’ data and radiographic images with AIS, with seven (7.69%) boys and 84 (92.31%). The overall mean Cobb angle was 32.9 ± 8.5º, and during brace treatment, it was 22.5 ± 11.5º. There was a significant mean difference in the mean Cobb angle before and in-brace (p < 0.001). The overall mean in-brace correction in the study was 34.1 ± 22.7%. Initial Cobb angle and BMI were found to be significantly negatively associated with in-brace correction with a Pearson coefficient of -0.49 and -0.24, respectively. Conclusion: The mean of first in-brace correction TLSO was 34.1% from the initial Cobb angle. No difference in in-brace correction across curve types in our study. There was a significant Cobb angle changed before and in-brace radiograph. We found that in-brace correction was significantly associated with initial Cobb angle and BMI. Keywords: Adolescent Idiopathic Scoliosis, in-brace correction, bracing